2019
DOI: 10.1002/aet2.10330
|View full text |Cite
|
Sign up to set email alerts
|

An Emergency Medicine Remediation Consult Service: Access to Expert Remediation Advice and Resources

Abstract: Resident remediation is a complex and common issue in emergency medicine programs and requires a specific knowledge base. The Remediation Task Force (RTF) of the Council of Residency Directors in Emergency Medicine (CORD-EM) was created to identify remediation best practices and to develop tools for program directors. Initially housed on a Wiki page, and now located within the CORD-EM website, the RTF provides resources including accepted universal language for documentation and sample remediation plans. The R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Emergency medicine (EM) program directors and core faculty are interested in identifying residents at risk of poor academic performance early in their training, preferably early in the first post-graduate year (PGY1). The Council of Emergency Medicine Residency Directors (CORD) concluded that successful remediation is dependent on early identification of poor performance [ 1 ] and created both a remediation task force and a remediation consult service to address these issues [ 2 ]. A 2014 survey [ 3 ] found that 90% of EM programs had at least one resident undergoing remediation, with medical knowledge as the most common indication for remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency medicine (EM) program directors and core faculty are interested in identifying residents at risk of poor academic performance early in their training, preferably early in the first post-graduate year (PGY1). The Council of Emergency Medicine Residency Directors (CORD) concluded that successful remediation is dependent on early identification of poor performance [ 1 ] and created both a remediation task force and a remediation consult service to address these issues [ 2 ]. A 2014 survey [ 3 ] found that 90% of EM programs had at least one resident undergoing remediation, with medical knowledge as the most common indication for remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Much has been previously written about feedback dynamics, and the graduate medical education community has placed a great deal of emphasis on the remediation of below‐expected clinical performance of residents 1–6 . Comparatively, little attention has been paid to the evaluation of expected‐ and high‐performing emergency medicine (EM) residents 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…Much has been previously written about feedback dynamics, and the graduate medical education community has placed a great deal of emphasis on the remediation of below-expected clinical performance of residents. [1][2][3][4][5][6] Comparatively, little attention has been paid to the evaluation of expected-and high-performing emergency medicine (EM) residents. [7][8][9] The conceptual framework of "deliberate practice," wherein learners of all skill levels can improve their clinical performance by incorporating immediate feedback, is the core idea for framing our research question.…”
Section: Introductionmentioning
confidence: 99%
“…Placing them on remediation or dismissing them is upsetting. 12 , 13 Further, it can be difficult to disarticulate mental health issues such as depression and borderline personality and substance use disorder from performance. Programs cannot dismiss trainees due to mental health concerns due to disability laws; however, they have the responsibility to act on unprofessional behavior and problematic clinical performance.…”
mentioning
confidence: 99%
“…As educators, we have compassion for trainees. Placing them on remediation or dismissing them is upsetting 12,13 . Further, it can be difficult to disarticulate mental health issues such as depression and borderline personality and substance use disorder from performance.…”
mentioning
confidence: 99%